A high-strength and high-toughness ceramic tool and preparation method thereof

By using the composite technology of iron ion-loaded boron nitride nanosheets with modified hydrotalcite and soy protein binders in ceramic tools, the problem of insufficient strength and toughness of ceramic tools is solved, and its mechanical properties and service life are significantly improved.

CN119285352BActive Publication Date: 2025-03-14JIANGSU YISDAR PRECISION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411450623.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-14
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The strength and toughness of traditional ceramic tools are insufficient, resulting in a short service life in high-speed cutting processes, which is prone to cracking and missing angles, affecting the performance of the use.

Method used

The mechanical strength and toughness of ceramic tools are improved by loading iron ions on the boron nitride nanosheets and combining with modified hydrotalcite and modified soy protein binder.

Benefits of technology

It significantly improves the bending strength and fracture toughness of ceramic tools, extends the service life, and reduces the occurrence of cracks and corners.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of tool manufacturing, specifically a high-strength and high-toughness ceramic tool and a preparation method thereof. The present invention loads metal ions on boron nitride nanosheets, and the loading of metal ions can improve the agglomeration phenomenon of boron nitride nanosheets, enhance the interaction force between boron nitride nanosheets, and thus improve the mechanical strength of boron nitride. The present invention utilizes the chelation of tannic acid and iron ions to form an adhesive complex on the boron nitride nanosheets, and utilizes its adhesiveness to adhere the boron nitride loaded with iron ions to the modified hydrotalcite. The modified soy protein prepared by the present invention has a large amount of amino groups, and the boron nitride-hydrotalcite complex with amino groups has better compatibility with the modified soy protein binder, improves the dispersibility of the boron nitride-hydrotalcite complex in the matrix, and improves the strength and toughness of the ceramic tool.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tool manufacturing, and in particular to a high-strength and high-toughness ceramic tool and a preparation method thereof. Background Art

[0002] High-speed cutting is one of the mainstream process technologies in metal cutting production practice in industrialized countries. As the cutting speed increases exponentially, the service life of the cutting tool will be greatly reduced. Therefore, it is becoming increasingly important to increase the service life of the cutting tool.

[0003] Compared with other tool materials, ceramic tools have insufficient fracture toughness and poor bending strength, and are prone to cracking and chipping, which affects performance. Therefore, traditional ceramic tools are no longer suitable for various high-strength and high-speed cutting processes required by modern scientific and technological development due to their strength limitations.

[0004] In order to solve the above problems and improve the strength and toughness of ceramic tools, the present invention provides a high-strength and high-toughness ceramic tool and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a high-strength and high-toughness ceramic tool and a preparation method thereof to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a high-strength and high-toughness ceramic tool comprises the following steps:

[0008] Step 1: Take boron nitride nanosheets and tannic acid aqueous solution, ultrasonicate for 20-30 minutes, stir for 1-2 hours, add phosphate buffer, adjust the pH value to 7.4, add ferric chloride aqueous solution, stir for 1-2 minutes, centrifuge, filter, and wash to obtain boron nitride loaded with iron ions;

[0009] Step 2: Take the boron nitride loaded with iron ions, the modified hydrotalcite, and deionized water, and ultrasonically disperse them for 30-40 minutes and stir them for 1-2 hours to obtain a boron nitride-hydrotalcite composite;

[0010] Step 3: Mix zirconium oxide, aluminum oxide, yttrium oxide, cerium oxide, lanthanum oxide, and boron nitride-hydrotalcite composite evenly, ball-mill, and sieve, add modified soybean protein binder, polyvinyl alcohol, and deionized water, mix evenly, ball-mill, calcine at 880-900°C for 60-70min, ball-mill, dry, sieve, and hot-press sinter at 1680-1700°C for 30-50min to obtain a high-strength and high-toughness ceramic tool.

[0011] More optimally, the ceramic cutting tool comprises the following ingredients, by weight: 60-65 parts of zirconium oxide, 25-32 parts of aluminum oxide, 5-7 parts of yttrium oxide, 8-9 parts of cerium oxide, 4-5 parts of lanthanum oxide, 2-3 parts of boron nitride-hydrotalcite composite, 2-3 parts of modified soy protein binder, 2-3 parts of polyvinyl alcohol, and 8-10 parts of deionized water.

[0012] More optimally, the preparation method of the modified hydrotalcite is: take ethanol and deionized water, stir evenly, add hydrotalcite powder, heat to 70-75°C, stir for 1-2h to obtain a hydrotalcite solution, add amination sodium lignin sulfonate and sodium lignin sulfonate, adjust the pH value to 3, stir for 3-4h, filter and dry to obtain the modified hydrotalcite.

[0013] More optimally, the preparation method of the hydrotalcite powder is: take zinc nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water, stir evenly, add anhydrous sodium carbonate and urea, stir evenly, adjust the pH value to 10, heat to 118-122°C, react for 22-26h, cool to 25-30°C, filter, wash, dry, and grind to obtain hydrotalcite powder.

[0014] More optimally, the preparation method of the amination sodium lignin sulfonate is: take ethanol and deionized water, stir evenly, add sodium lignin sulfonate, stir at 30-35°C for 1-2h, add a mixture of ethylenediamine and ethylene glycol, adjust the pH value to 11, heat to 80-85°C, add glutaraldehyde, stir for 4-5h, add ethanol, centrifuge for 30-40min, dry and grind to obtain amination sodium lignin sulfonate.

[0015] More optimally, the preparation method of the modified soy protein binder is: take soy protein isolate and deionized water, stir for 20-30 minutes, add oxidized sodium alginate, and stir for 30-40 minutes to obtain the modified soy protein binder.

[0016] More optimally, the preparation method of oxidized sodium alginate is: take sodium alginate and deionized water, stir for 2-3 hours to obtain a sodium alginate solution, add sodium periodate dropwise, then stir for 22-26 hours under light-proof conditions, add ethylene glycol, stir for 30-40 minutes under light-proof conditions, dialyze, and freeze-dry to obtain oxidized sodium alginate.

[0017] More optimally, in step 2, the mass ratio of boron nitride loaded with iron ions, modified hydrotalcite, and deionized water is: (1-3): 1:250.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] (1) The present invention loads metal ions on boron nitride nanosheets. The loading of metal ions can improve the agglomeration of boron nitride nanosheets and enhance the interaction between boron nitride nanosheets, thereby improving the mechanical strength of boron nitride. The present invention utilizes the chelation of tannic acid and iron ions to form an adhesive complex on the boron nitride nanosheets, and utilizes the adhesiveness to adhere the boron nitride loaded with iron ions to the modified hydrotalcite.

[0020] (2) Hydrotalcite has the characteristics of high strength and high toughness, and can effectively enhance the strength and toughness of ceramic cutting tools. The present invention uses aminated sodium lignin sulfonate to intercalate hydrotalcite, thereby increasing the interlayer spacing of hydrotalcite and the specific surface area of ​​hydrotalcite, so that it can load more boron nitride, further improving the strength and toughness of ceramic cutting tools.

[0021] Soy protein isolate is modified with sodium alginate. The addition of sodium alginate increases the cross-linking density of soy protein, thereby improving the bonding effect of the modified soy protein binder. Modified soy protein has a large number of amino groups, and the boron nitride-hydrotalcite composite with amino groups has better compatibility with the modified soy protein binder, which improves the dispersibility of the boron nitride-hydrotalcite composite in the matrix and improves the strength and toughness of the ceramic tool. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] There is no particular restriction on the manufacturers of all raw materials in the present invention, and exemplary examples include: soy protein isolate: model: SD-301, which can be purchased from Linyi Shansong Biological Products Co., Ltd.; boron nitride nanosheets: sheet diameter 0.5-5μm, thickness: 50nm; polyvinyl alcohol: model: QSC-PVA1788, which can be purchased from Wuhan Runxingyuan Technology Co., Ltd.

[0024] Embodiment 1: A method for preparing a high-strength and high-toughness ceramic tool, comprising the following steps:

[0025] Step 1: Preparation of hydrotalcite:

[0026] Take 6 g of zinc nitrate hexahydrate, 3.8 g of aluminum nitrate nonahydrate, and 60 mL of deionized water, stir evenly, add 2.6 g of anhydrous sodium carbonate and 1.8 g of urea, stir evenly, adjust the pH value to 10, heat to 120°C, react for 24 hours, cool to 27°C, filter, wash, dry, and grind to obtain hydrotalcite powder;

[0027] Step 2: Preparation of amination sodium lignin sulfonate:

[0028] Take 100 mL of ethanol and 100 mL of deionized water, stir evenly, add 2 g of sodium lignin sulfonate, stir at 32 ° C for 1.5 h, add a mixture of 6 g of ethylenediamine and 6 g of ethylene glycol, adjust the pH value to 11, heat to 83 ° C, add 1 mL of glutaraldehyde, stir for 4.5 h, add 300 mL of ethanol, centrifuge for 35 min, dry and grind to obtain amination sodium lignin sulfonate;

[0029] Step 3: Preparation of modified hydrotalcite:

[0030] Take 200 mL of ethanol and 200 mL of deionized water, stir evenly, add 1.2 g of hydrotalcite powder, heat to 73 ° C, stir for 1.5 h to obtain a hydrotalcite solution, add 0.15 g of amination sodium lignin sulfonate and 0.1 g of sodium lignin sulfonate, adjust the pH value to 3, stir for 3.5 h, filter and dry to obtain modified hydrotalcite;

[0031] Step 4: Preparation of modified soy protein binder:

[0032] Take 10g of sodium alginate and 700mL of deionized water, stir for 2.5h to obtain a sodium alginate solution, add 50mL of 0.93mol / L sodium periodate dropwise, then stir for 24h in a dark environment, add 4mL of ethylene glycol, stir for 35min in a dark environment, dialyze, and freeze-dry to obtain oxidized sodium alginate;

[0033] Take 30g of soy protein isolate and 180mL of deionized water, stir for 25min, add 2.5g of oxidized sodium alginate, stir for 35min, and obtain a modified soy protein binder;

[0034] Step 5: Preparation of Boron Nitride Loaded with Iron Ions:

[0035] Take 0.5 g of boron nitride nanosheets and 200 mL of 0.2 mg / mL tannic acid aqueous solution, ultrasonicate for 25 min, stir for 1.5 h, add phosphate buffer, adjust the pH value to 7.4, add 1 mL of 6 mg / mL ferric chloride aqueous solution, stir for 1.5 min, centrifuge, filter, and wash to obtain boron nitride loaded with iron ions;

[0036] Step 6: Preparation of boron nitride-hydrotalcite composite:

[0037] Take 2 g of iron-loaded boron nitride, 1 g of modified hydrotalcite, and 500 mL of deionized water, ultrasonically disperse for 35 min, and stir for 1.5 h to obtain a boron nitride-hydrotalcite composite;

[0038] The mass ratio of boron nitride loaded with iron ions, modified hydrotalcite, and deionized water is 2:1:250;

[0039] Step 7: Preparation method of ceramic knives:

[0040] Zirconia, aluminum oxide, yttrium oxide, cerium oxide, lanthanum oxide, boron nitride-hydrotalcite composite, mixed evenly, ball milled, passed through a 200-mesh sieve, added with modified soybean protein binder, polyvinyl alcohol, and deionized water, mixed evenly, ball milled, calcined at 890°C for 65 minutes, ball milled, dried, passed through a 60-mesh sieve, and hot-pressed sintered at 1690°C, with a pressure of 30 MPa for 40 minutes to obtain a high-strength and high-toughness ceramic tool;

[0041] The ceramic cutting tool comprises the following components, measured by weight:

[0042] 63 parts of zirconium oxide, 30 parts of aluminum oxide, 6 parts of yttrium oxide, 8.5 parts of cerium oxide, 4.5 parts of lanthanum oxide, 2.5 parts of boron nitride-hydrotalcite composite, 2.5 parts of modified soybean protein binder, 2.5 parts of polyvinyl alcohol, and 9 parts of deionized water.

[0043] Embodiment 2: A method for preparing a high-strength and high-toughness ceramic tool, comprising the following steps:

[0044] Step 1: Preparation of hydrotalcite:

[0045] Take 6 g of zinc nitrate hexahydrate, 3.8 g of aluminum nitrate nonahydrate, and 60 mL of deionized water, stir evenly, add 2.6 g of anhydrous sodium carbonate and 1.8 g of urea, stir evenly, adjust the pH value to 10, heat to 118°C, react for 22 hours, cool to 25°C, filter, wash, dry, and grind to obtain hydrotalcite powder;

[0046] Step 2: Preparation of amination sodium lignin sulfonate:

[0047] Take 100 mL of ethanol and 100 mL of deionized water, stir evenly, add 2 g of sodium lignin sulfonate, stir at 30 ° C for 1 h, add a mixture of 6 g of ethylenediamine and 6 g of ethylene glycol, adjust the pH value to 11, heat to 80 ° C, add 1 mL of glutaraldehyde, stir for 4 h, add 300 mL of ethanol, centrifuge for 30 min, dry and grind to obtain amination sodium lignin sulfonate;

[0048] Step 3: Preparation of modified hydrotalcite:

[0049] Take 200 mL of ethanol and 200 mL of deionized water, stir evenly, add 1.2 g of hydrotalcite powder, heat to 70 ° C, stir for 1 h to obtain a hydrotalcite solution, add 0.15 g of amination sodium lignin sulfonate and 0.1 g of sodium lignin sulfonate, adjust the pH value to 3, stir for 3 h, filter and dry to obtain modified hydrotalcite;

[0050] Step 4: Preparation of modified soy protein binder:

[0051] Take 10g of sodium alginate and 700mL of deionized water, stir for 2h to obtain a sodium alginate solution, add 50mL of 0.93mol / L sodium periodate dropwise, then stir for 22h in a dark environment, add 4mL of ethylene glycol, stir for 30min in a dark environment, dialyze, and freeze-dry to obtain oxidized sodium alginate;

[0052] Take 30g of soy protein isolate and 180mL of deionized water, stir for 20min, add 2.5g of oxidized sodium alginate, stir for 30min, and obtain a modified soy protein binder;

[0053] Step 5: Preparation of Boron Nitride Loaded with Iron Ions:

[0054] Take 0.5 g of boron nitride nanosheets and 200 mL of 0.2 mg / mL tannic acid aqueous solution, ultrasonicate for 20 min, stir for 1 h, add phosphate buffer, adjust the pH value to 7.4, add 1 mL of 6 mg / mL ferric chloride aqueous solution, stir for 1 min, centrifuge, filter, and wash to obtain boron nitride loaded with iron ions;

[0055] Step 6: Preparation of boron nitride-hydrotalcite composite:

[0056] Take 2 g of iron-loaded boron nitride, 2 g of modified hydrotalcite, and 500 mL of deionized water, ultrasonically disperse for 30 min, and stir for 1 h to obtain a boron nitride-hydrotalcite composite;

[0057] The mass ratio of boron nitride loaded with iron ions, modified hydrotalcite, and deionized water is 1:1:250;

[0058] Step 7: Preparation method of ceramic knives:

[0059] Zirconia, aluminum oxide, yttrium oxide, cerium oxide, lanthanum oxide, boron nitride-hydrotalcite composite, mixed evenly, ball milled, passed through a 200-mesh sieve, added with modified soybean protein binder, polyvinyl alcohol, and deionized water, mixed evenly, ball milled, calcined at 880°C for 60 minutes, ball milled, dried, passed through a 60-mesh sieve, and hot-pressed sintered at 1680°C, with a pressure of 30 MPa for 30 minutes to obtain a high-strength and high-toughness ceramic tool;

[0060] The ceramic cutting tool comprises the following components, measured by weight:

[0061] 60 parts of zirconium oxide, 25 parts of aluminum oxide, 5 parts of yttrium oxide, 8 parts of cerium oxide, 4 parts of lanthanum oxide, 2 parts of boron nitride-hydrotalcite composite, 2 parts of modified soybean protein binder, 2 parts of polyvinyl alcohol, and 8 parts of deionized water.

[0062] Embodiment 3: A method for preparing a high-strength and high-toughness ceramic tool, comprising the following steps:

[0063] Step 1: Preparation of hydrotalcite:

[0064] Take 6 g of zinc nitrate hexahydrate, 3.8 g of aluminum nitrate nonahydrate, and 60 mL of deionized water, stir evenly, add 2.6 g of anhydrous sodium carbonate and 1.8 g of urea, stir evenly, adjust the pH value to 10, heat to 122°C, react for 26 hours, cool to 30°C, filter, wash, dry, and grind to obtain hydrotalcite powder;

[0065] Step 2: Preparation of amination sodium lignin sulfonate:

[0066] Take 100 mL of ethanol and 100 mL of deionized water, stir evenly, add 2 g of sodium lignin sulfonate, stir at 35 ° C for 2 h, add a mixture of 6 g of ethylenediamine and 6 g of ethylene glycol, adjust the pH value to 11, heat to 85 ° C, add 1 mL of glutaraldehyde, stir for 5 h, add 300 mL of ethanol, centrifuge for 40 min, dry and grind to obtain amination sodium lignin sulfonate;

[0067] Step 3: Preparation of modified hydrotalcite:

[0068] Take 200 mL of ethanol and 200 mL of deionized water, stir evenly, add 1.2 g of hydrotalcite powder, heat to 75 ° C, stir for 2 h to obtain a hydrotalcite solution, add 0.15 g of amination sodium lignin sulfonate and 0.1 g of sodium lignin sulfonate, adjust the pH value to 3, stir for 4 h, filter and dry to obtain modified hydrotalcite;

[0069] Step 4: Preparation of modified soy protein binder:

[0070] Take 10g of sodium alginate and 700mL of deionized water, stir for 3h to obtain a sodium alginate solution, add 50mL of 0.93mol / L sodium periodate dropwise, then stir for 26h in a dark environment, add 4mL of ethylene glycol, stir for 40min in a dark environment, dialyze, and freeze-dry to obtain oxidized sodium alginate;

[0071] Take 30g of soy protein isolate and 180mL of deionized water, stir for 30min, add 2.5g of oxidized sodium alginate, stir for 40min, and obtain a modified soy protein binder;

[0072] Step 5: Preparation of Boron Nitride Loaded with Iron Ions:

[0073] Take 0.5 g of boron nitride nanosheets and 200 mL of 0.2 mg / mL tannic acid aqueous solution, ultrasonicate for 30 min, stir for 2 h, add phosphate buffer, adjust the pH value to 7.4, add 1 mL of 6 mg / mL ferric chloride aqueous solution, stir for 2 min, centrifuge, filter, and wash to obtain boron nitride loaded with iron ions;

[0074] Step 6: Preparation of boron nitride-hydrotalcite composite:

[0075] Take 3 g of iron ion-loaded boron nitride, 2 g of modified hydrotalcite, and 500 mL of deionized water, ultrasonically disperse for 40 min, and stir for 2 h to obtain a boron nitride-hydrotalcite composite;

[0076] The mass ratio of boron nitride loaded with iron ions, modified hydrotalcite, and deionized water is 3:1:250;

[0077] Step 7: Preparation method of ceramic knives:

[0078] Zirconia, aluminum oxide, yttrium oxide, cerium oxide, lanthanum oxide, boron nitride-hydrotalcite composite, mixed evenly, ball milled, passed through a 200-mesh sieve, added with modified soybean protein binder, polyvinyl alcohol, and deionized water, mixed evenly, ball milled, calcined at 900°C for 70 minutes, ball milled, dried, passed through a 60-mesh sieve, and hot-pressed sintered at 1700°C, with a pressure of 30 MPa for 50 minutes to obtain a high-strength and high-toughness ceramic tool;

[0079] The ceramic cutting tool comprises the following components, measured by weight:

[0080] 65 parts of zirconium oxide, 32 parts of aluminum oxide, 7 parts of yttrium oxide, 9 parts of cerium oxide, 5 parts of lanthanum oxide, 3 parts of boron nitride-hydrotalcite composite, 3 parts of modified soybean protein binder, 3 parts of polyvinyl alcohol, and 10 parts of deionized water.

[0081] Comparative Example 1: No metal ions are present on the boron nitride nanosheets, and the rest is the same as in Example 1:

[0082] Step 1: Preparation of hydrotalcite:

[0083] Take 6 g of zinc nitrate hexahydrate, 3.8 g of aluminum nitrate nonahydrate, and 60 mL of deionized water, stir evenly, add 2.6 g of anhydrous sodium carbonate and 1.8 g of urea, stir evenly, adjust the pH value to 10, heat to 120°C, react for 24 hours, cool to 27°C, filter, wash, dry, and grind to obtain hydrotalcite powder;

[0084] Step 2: Preparation of amination sodium lignin sulfonate:

[0085] Take 100 mL of ethanol and 100 mL of deionized water, stir evenly, add 2 g of sodium lignin sulfonate, stir at 32 ° C for 1.5 h, add a mixture of 6 g of ethylenediamine and 6 g of ethylene glycol, adjust the pH value to 11, heat to 83 ° C, add 1 mL of glutaraldehyde, stir for 4.5 h, add 300 mL of ethanol, centrifuge for 35 min, dry and grind to obtain amination sodium lignin sulfonate;

[0086] Step 3: Preparation of modified hydrotalcite:

[0087] Take 200 mL of ethanol and 200 mL of deionized water, stir evenly, add 1.2 g of hydrotalcite powder, heat to 73 ° C, stir for 1.5 h to obtain a hydrotalcite solution, add 0.15 g of amination sodium lignin sulfonate and 0.1 g of sodium lignin sulfonate, adjust the pH value to 3, stir for 3.5 h, filter and dry to obtain modified hydrotalcite;

[0088] Step 4: Preparation of modified soy protein binder:

[0089] Take 10g of sodium alginate and 700mL of deionized water, stir for 2.5h to obtain a sodium alginate solution, add 50mL of 0.93mol / L sodium periodate dropwise, then stir for 24h in a dark environment, add 4mL of ethylene glycol, stir for 35min in a dark environment, dialyze, and freeze-dry to obtain oxidized sodium alginate;

[0090] Take 30g of soy protein isolate and 180mL of deionized water, stir for 25min, add 2.5g of oxidized sodium alginate, stir for 35min, and obtain a modified soy protein binder;

[0091] Step 5: Preparation of modified boron nitride:

[0092] Take 0.5 g of boron nitride nanosheets and 200 mL of 0.2 mg / mL tannic acid aqueous solution, ultrasonicate for 25 min, stir for 1.5 h, add phosphate buffer, adjust the pH value to 7.4, centrifuge, filter, and wash to obtain modified boron nitride;

[0093] Step 6: Preparation of boron nitride-hydrotalcite composite:

[0094] Take 2 g of modified boron nitride, 1 g of modified hydrotalcite, and 500 mL of deionized water, ultrasonically disperse for 35 min, and stir for 1.5 h to obtain a boron nitride-hydrotalcite composite;

[0095] Step 7: Preparation method of ceramic knives:

[0096] Zirconia, aluminum oxide, yttrium oxide, cerium oxide, lanthanum oxide, boron nitride-hydrotalcite composite, mixed evenly, ball milled, passed through a 200-mesh sieve, added with modified soybean protein binder, polyvinyl alcohol, and deionized water, mixed evenly, ball milled, calcined at 890°C for 65 minutes, ball milled, dried, passed through a 60-mesh sieve, and hot-pressed sintered at 1690°C, with a pressure of 30 MPa for 40 minutes to obtain a high-strength and high-toughness ceramic tool;

[0097] The ceramic cutting tool comprises the following components, measured by weight:

[0098] 63 parts of zirconium oxide, 30 parts of aluminum oxide, 6 parts of yttrium oxide, 8.5 parts of cerium oxide, 4.5 parts of lanthanum oxide, 2.5 parts of boron nitride-hydrotalcite composite, 2.5 parts of modified soybean protein binder, 2.5 parts of polyvinyl alcohol, and 9 parts of deionized water.

[0099] Comparative Example 2: The hydrotalcite is not intercalated with ammoniated sodium lignin sulfonate, and the rest is the same as Example 1:

[0100] Step 1: Preparation of hydrotalcite:

[0101] Take 6 g of zinc nitrate hexahydrate, 3.8 g of aluminum nitrate nonahydrate, and 60 mL of deionized water, stir evenly, add 2.6 g of anhydrous sodium carbonate and 1.8 g of urea, stir evenly, adjust the pH value to 10, heat to 120°C, react for 24 hours, cool to 27°C, filter, wash, dry, and grind to obtain hydrotalcite powder;

[0102] Step 2: Preparation of modified hydrotalcite:

[0103] Take 200 mL of ethanol and 200 mL of deionized water, stir evenly, add 1.2 g of hydrotalcite powder, heat to 73 ° C, stir for 1.5 h to obtain a hydrotalcite solution, add 0.25 g of sodium lignin sulfonate, adjust the pH value to 3, stir for 3.5 h, filter and dry to obtain modified hydrotalcite;

[0104] Step 3: Preparation of modified soy protein binder:

[0105] Take 10g of sodium alginate and 700mL of deionized water, stir for 2.5h to obtain a sodium alginate solution, add 50mL of 0.93mol / L sodium periodate dropwise, then stir for 24h in a dark environment, add 4mL of ethylene glycol, stir for 35min in a dark environment, dialyze, and freeze-dry to obtain oxidized sodium alginate;

[0106] Take 30g of soy protein isolate and 180mL of deionized water, stir for 25min, add 2.5g of oxidized sodium alginate, stir for 35min, and obtain a modified soy protein binder;

[0107] Step 4: Preparation of Boron Nitride Loaded with Iron Ions:

[0108] Take 0.5 g of boron nitride nanosheets and 200 mL of 0.2 mg / mL tannic acid aqueous solution, ultrasonicate for 25 min, stir for 1.5 h, add phosphate buffer, adjust the pH value to 7.4, add 1 mL of 6 mg / mL ferric chloride aqueous solution, stir for 1.5 min, centrifuge, filter, and wash to obtain boron nitride loaded with iron ions;

[0109] Step 5: Preparation of boron nitride-hydrotalcite composite:

[0110] Take 2 g of iron-loaded boron nitride, 1 g of modified hydrotalcite, and 500 mL of deionized water, ultrasonically disperse for 35 min, and stir for 1.5 h to obtain a boron nitride-hydrotalcite composite;

[0111] The mass ratio of boron nitride loaded with iron ions, modified hydrotalcite, and deionized water is 2:1:250;

[0112] Step 6: Preparation method of ceramic knives:

[0113] Zirconia, aluminum oxide, yttrium oxide, cerium oxide, lanthanum oxide, boron nitride-hydrotalcite composite, mixed evenly, ball milled, passed through a 200-mesh sieve, added with modified soybean protein binder, polyvinyl alcohol, and deionized water, mixed evenly, ball milled, calcined at 890°C for 65 minutes, ball milled, dried, passed through a 60-mesh sieve, and hot-pressed sintered at 1690°C, with a pressure of 30 MPa for 40 minutes to obtain a high-strength and high-toughness ceramic tool;

[0114] The ceramic cutting tool comprises the following components, measured by weight:

[0115] 63 parts of zirconium oxide, 30 parts of aluminum oxide, 6 parts of yttrium oxide, 8.5 parts of cerium oxide, 4.5 parts of lanthanum oxide, 2.5 parts of boron nitride-hydrotalcite composite, 2.5 parts of modified soybean protein binder, 2.5 parts of polyvinyl alcohol, and 9 parts of deionized water.

[0116] Comparative Example 3: Sodium alginate is not used to modify the soy protein isolate, and the rest is the same as Example 1:

[0117] Step 1: Preparation of hydrotalcite:

[0118] Take 6 g of zinc nitrate hexahydrate, 3.8 g of aluminum nitrate nonahydrate, and 60 mL of deionized water, stir evenly, add 2.6 g of anhydrous sodium carbonate and 1.8 g of urea, stir evenly, adjust the pH value to 10, heat to 120°C, react for 24 hours, cool to 27°C, filter, wash, dry, and grind to obtain hydrotalcite powder;

[0119] Step 2: Preparation of amination sodium lignin sulfonate:

[0120] Take 100 mL of ethanol and 100 mL of deionized water, stir evenly, add 2 g of sodium lignin sulfonate, stir at 32 ° C for 1.5 h, add a mixture of 6 g of ethylenediamine and 6 g of ethylene glycol, adjust the pH value to 11, heat to 83 ° C, add 1 mL of glutaraldehyde, stir for 4.5 h, add 300 mL of ethanol, centrifuge for 35 min, dry and grind to obtain amination sodium lignin sulfonate;

[0121] Step 3: Preparation of modified hydrotalcite:

[0122] Take 200 mL of ethanol and 200 mL of deionized water, stir evenly, add 1.2 g of hydrotalcite powder, heat to 73 ° C, stir for 1.5 h to obtain a hydrotalcite solution, add 0.15 g of amination sodium lignin sulfonate and 0.1 g of sodium lignin sulfonate, adjust the pH value to 3, stir for 3.5 h, filter and dry to obtain modified hydrotalcite;

[0123] Step 4: Preparation of soy protein binder:

[0124] Take 30 g of soy protein isolate and 180 mL of deionized water, stir for 60 min to obtain a soy protein binder;

[0125] Step 5: Preparation of Boron Nitride Loaded with Iron Ions:

[0126] Take 0.5 g of boron nitride nanosheets and 200 mL of 0.2 mg / mL tannic acid aqueous solution, ultrasonicate for 25 min, stir for 1.5 h, add phosphate buffer, adjust the pH value to 7.4, add 1 mL of 6 mg / mL ferric chloride aqueous solution, stir for 1.5 min, centrifuge, filter, and wash to obtain boron nitride loaded with iron ions;

[0127] Step 5: Preparation of boron nitride-hydrotalcite composite:

[0128] Take 2 g of iron-loaded boron nitride, 1 g of modified hydrotalcite, and 500 mL of deionized water, ultrasonically disperse for 35 min, and stir for 1.5 h to obtain a boron nitride-hydrotalcite composite;

[0129] The mass ratio of boron nitride loaded with iron ions, modified hydrotalcite, and deionized water is 2:1:250;

[0130] Step 6: Preparation method of ceramic knives:

[0131] Zirconia, aluminum oxide, yttrium oxide, cerium oxide, lanthanum oxide, boron nitride-hydrotalcite composite, mixed evenly, ball milled, passed through a 200-mesh sieve, added with soybean protein binder, polyvinyl alcohol, and deionized water, mixed evenly, ball milled, calcined at 890°C for 65 minutes, ball milled, dried, passed through a 60-mesh sieve, and hot-pressed sintered at 1690°C, with a pressure of 30 MPa for 40 minutes to obtain a high-strength and high-toughness ceramic tool;

[0132] The ceramic cutting tool comprises the following components, measured by weight:

[0133] 63 parts of zirconium oxide, 30 parts of aluminum oxide, 6 parts of yttrium oxide, 8.5 parts of cerium oxide, 4.5 parts of lanthanum oxide, 2.5 parts of boron nitride-hydrotalcite composite, 2.5 parts of soybean protein binder, 2.5 parts of polyvinyl alcohol, and 9 parts of deionized water.

[0134] experiment:

[0135] The mechanical properties of the ceramic cutting tools prepared in Examples 1-3 and Comparative Examples 1-3 were tested, and the obtained data are shown in the following table:

[0136] Bending strength / MPa Fracture toughness / MPa·m1 / 2 Example 1 1632 18 Example 2 1625 18 Example 3 1636 18 Comparative Example 1 1565 16 Comparative Example 2 1581 17 Comparative Example 3 1607 17

[0137] Conclusion: In Comparative Example 1, metal ions are not loaded on boron nitride nanosheets, the adhesion between boron nitride loaded with iron ions and modified hydrotalcite decreases, and the strength and toughness of the ceramic tool decrease. In Comparative Example 2, aminated sodium lignin sulfonate is not used to intercalate hydrotalcite, and the compatibility of boron nitride-hydrotalcite composite with modified soybean protein binder deteriorates, affecting the strength and toughness of the ceramic tool. In Comparative Example 3, sodium alginate is not used to modify soybean protein isolate, the crosslinking density of soybean protein decreases, the viscosity of the binder decreases, and the strength and toughness of the ceramic tool decrease.

[0138] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength and high-toughness ceramic tool, characterized in that: The following steps are involved: Step 1: Take boron nitride nanosheets and tannic acid aqueous solution, ultrasonicate for 20-30 minutes, stir for 1-2 hours, add phosphate buffer, adjust the pH value to 7.4, add ferric chloride aqueous solution, stir for 1-2 minutes, centrifuge, filter, and wash to obtain boron nitride loaded with iron ions; Step 2: Take the boron nitride loaded with iron ions, the modified hydrotalcite, and deionized water, and ultrasonically disperse them for 30-40 minutes and stir them for 1-2 hours to obtain a boron nitride-hydrotalcite composite; Step 3: Mix zirconium oxide, aluminum oxide, yttrium oxide, cerium oxide, lanthanum oxide, and boron nitride-hydrotalcite composite evenly, ball-mill, and sieve, add modified soybean protein binder, polyvinyl alcohol, and deionized water, mix evenly, ball-mill, calcine at 880-900°C for 60-70min, ball-mill, dry, sieve, and hot-press sinter at 1680-1700°C for 30-50min to obtain a high-strength and high-toughness ceramic tool.

2. The method for preparing a high-strength and high-toughness ceramic tool according to claim 1, characterized in that: The ceramic cutting tool comprises the following ingredients, by weight: 60-65 parts of zirconium oxide, 25-32 parts of aluminum oxide, 5-7 parts of yttrium oxide, 8-9 parts of cerium oxide, 4-5 parts of lanthanum oxide, 2-3 parts of boron nitride-hydrotalcite composite, 2-3 parts of modified soy protein binder, 2-3 parts of polyvinyl alcohol, and 8-10 parts of deionized water.

3. The method for preparing a high-strength and high-toughness ceramic tool according to claim 1, characterized in that: The preparation method of the modified hydrotalcite is as follows: take ethanol and deionized water, stir evenly, add hydrotalcite powder, heat to 70-75° C., stir for 1-2 hours to obtain a hydrotalcite solution, add amination sodium lignin sulfonate and sodium lignin sulfonate, adjust the pH value to 3, stir for 3-4 hours, filter and dry to obtain the modified hydrotalcite.

4. The method for preparing a high-strength and high-toughness ceramic tool according to claim 3, characterized in that: The preparation method of the hydrotalcite powder is as follows: taking zinc nitrate hexahydrate, aluminum nitrate nonahydrate and deionized water, stirring evenly, adding anhydrous sodium carbonate and urea, stirring evenly, adjusting the pH value to 10, heating to 118-122° C., reacting for 22-26 hours, cooling to 25-30° C., filtering, washing, drying and grinding to obtain the hydrotalcite powder.

5. The method for preparing a high-strength and high-toughness ceramic tool according to claim 3, characterized in that: The preparation method of the amination sodium lignin sulfonate comprises the following steps: taking ethanol and deionized water, stirring evenly, adding sodium lignin sulfonate, stirring at 30-35°C for 1-2h, adding a mixture of ethylenediamine and ethylene glycol, adjusting the pH value to 11, heating to 80-85°C, adding glutaraldehyde, stirring for 4-5h, adding ethanol, centrifuging for 30-40min, drying, and grinding to obtain the amination sodium lignin sulfonate.

6. The method for preparing a high-strength and high-toughness ceramic tool according to claim 1, characterized in that: The preparation method of the modified soybean protein binder is as follows: taking soybean protein isolate and deionized water, stirring for 20-30 minutes, adding oxidized sodium alginate, and stirring for 30-40 minutes to obtain the modified soybean protein binder.

7. The method for preparing a high-strength and high-toughness ceramic tool according to claim 6, characterized in that: The preparation method of the oxidized sodium alginate is as follows: sodium alginate and deionized water are taken, stirred for 2-3 hours to obtain a sodium alginate solution, sodium periodate is added dropwise, and then stirred for 22-26 hours under light-proof conditions, ethylene glycol is added, stirred for 30-40 minutes under light-proof conditions, dialyzed, and freeze-dried to obtain the oxidized sodium alginate.

8. The method for preparing a high-strength and high-toughness ceramic tool according to claim 1, characterized in that: In step 2, the mass ratio of boron nitride loaded with iron ions, modified hydrotalcite, and deionized water is: (1-3): 1:

250.

9. A ceramic tool prepared according to the method for preparing a high-strength and high-toughness ceramic tool according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Flame retardant ceramic eyelet

    CN104844169A

  • High-strength and high-toughness ceramic composite material and application thereof to manufacturing of cutter

    CN106278254A